Trend of myopia through different interventions from 2010 to 2050: Findings from Eastern Chinese student surveillance study - Zhang, Xiyan; Zhou, Yonlin; Wang, Yan; Du, Wei; Yang, Jie (Frontiers in Medicine, 2023)
Purpose: Firstly, to investigate the utilization rate and effect of proven myopic interventions. Second, to predict the prevalence of myopia and high myopia, as well as YLD caused by an uncorrected refractive error in children and teens in eastern China from 2010 to 2050 under different interventions. Methods: 1) The surveillance of common diseases among children and adolescents in Jiangsu Province from 2010 to 2021 provides the database for myopia screening and intervention utilization surveys. 2) The National Bureau of Statistics and the Global Burden of Disease Study 2016 (GBD2016) are the foundation for the estimated myopes and YLD. 3) A systematic review provides the strong or weak impact of intervention in the prediction model.4) The trend of screening myopia from 2010 to 2050 under various treatments is predicted using a GM (1,1) model. Results: Myopia is expected to affect 8,568,305 (7–12 years old) and 15,766,863 (13–18 years old) children and adolescents, respectively, by the year 2050 (95%CI: 8,398,977-8,737,633).The utilization prevalence of myopia-proven interventions for myopic children included outdoor activities, orthokeratology lenses, atropine treatment, contact lenses, frame glasses, and eye exercises, with respective rates of 31.9-33.1 percent, 2.1-2.3 percent, 6.0-7.5 percent, 2.2-2.7 percent, 60.4-62.2 percent, and 64.7-72.5 percent. All interventions have substantial effects on myopia after parental myopia and behavior pattern adjustment, including physical activity, near work, dietary pattern, and sleep. Under strong intervention, the estimated reduced myopia prevalence by the year 2050 is 1,259,086 (95 %CI: 1,089,758-1,428,414) for children aged 7 to 12, and 584,785 (95 %CI: 562,748-606,823) for children aged 13 to 18, respectively. Conclusion: Among myopic Chinese children and adolescents, the use rates and effects of proven myopia interventions vary. Under the present intervention strategy, the prevalence of myopia and high myopia will increase from 2010 to 2050. The overall number of myopic people can be greatly decreased by implementing timely, steady, comprehensive interventions.